2005
DOI: 10.1007/s00268-005-0060-7
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Response of Autogenous Splenic Tissue Implanted in the Abdominal Cavity of Mice

Abstract: There is still controversy about the immunologic function of autotransplanted splenic tissue. In this study, splenic autotransplantation was performed in the abdominal cavity of mice, and the plaqueforming cell (PFC) assay was used to investigate the frequency of antibody-forming cells in response to sheep red blood cell (SRBC) immunization. BALB/c mice were divided into four groups according to the location of the autogenous graft: intraomental (IO), free peritoneal splenosis (FPS), retroperitoneal (RP), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
11
0
7

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 33 publications
1
11
0
7
Order By: Relevance
“…However, because the spleen is the organ most affected in closed abdominal trauma, and because the conservation techniques are not widely known, the incidence of total splenectomy is still rising. In addition, the partial or total mending of the spleen in its anatomical site was always considered difficult [1,6].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, because the spleen is the organ most affected in closed abdominal trauma, and because the conservation techniques are not widely known, the incidence of total splenectomy is still rising. In addition, the partial or total mending of the spleen in its anatomical site was always considered difficult [1,6].…”
mentioning
confidence: 99%
“…Because of the growing recognition of its importance, splenic preservation is becoming more desirable in the treatment of splenic injuries [5,6]. Several techniques that preserve the integral or partial spleen have been described, such as splenorrhaphy, partial splenectomy, subtotal splenectomy, arterial ligatures, application of hemostatic agents, and splenic implants [7,8].…”
mentioning
confidence: 99%
“…Many experimental studies have shown that animals that had underwent autotransplantation of splenic fragments experienced less infections in comparison to those that underwent total splenectomy alone (8,12). However, it should be stressed that the mere presence of splenic tissue as auto-transplantation does not necessarily imply normal immune function and that infection rates in the group with healthy normal spleens is significantly lower than the group in which total splenectomy and autotransplantation of splenic fragments was performed (13).…”
Section: Discussionmentioning
confidence: 99%
“…Autogenous transplantation of splenic tissue is an alternative for preservation of splenic functions when total splenectomy is inevitable (5). In this work, SP animals presented greater capacity for controlling infection by L. monocytogenes than animals in the CT and AT groups.…”
Section: Discussionmentioning
confidence: 99%
“…In order to maintain functions of the spleen when total splenectomy is inevitable, methods such as autogenous grafting of the spleen (5–7) have been used to preserve splenic tissue. Implantation of splenic fragments in different sites in the abdomen is based on splenosis and is not a novel practice (8).…”
mentioning
confidence: 99%